2020
DOI: 10.12709/mest.08.08.02.09
|View full text |Cite
|
Sign up to set email alerts
|

European Territorial Cooperation as a Factor of Tourism Development

Abstract: The article presents the outcome of qualitative and quantitative research methods applied by the authors to evaluate benefits and obstacles of the cross-border INTERREG program between Hungary and the Slovak Republic from 2014 to 2020, as one of the tools of European territorial cooperation for tourism development concerning bordering regions of Slovakia. This article aims to provide a recipient with a verified research method and results of the analysis to encourage more efficient employment of the European t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…But when it comes to obstacles related to financing cross-border cooperation, the biggest problem for stakeholders is the financing model of Interreg projects. This model of reimbursement of eligible expenditures for the implementation of projects is complicated and lengthy (Filip et al 2020). The requirement of own contribution on the part of the beneficiary, as well as the lack of advance payments, significantly limit the participation in the program of institutions which, for financial reasons, would not be able to cover the costs of project implementation (Dołzbłasz 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But when it comes to obstacles related to financing cross-border cooperation, the biggest problem for stakeholders is the financing model of Interreg projects. This model of reimbursement of eligible expenditures for the implementation of projects is complicated and lengthy (Filip et al 2020). The requirement of own contribution on the part of the beneficiary, as well as the lack of advance payments, significantly limit the participation in the program of institutions which, for financial reasons, would not be able to cover the costs of project implementation (Dołzbłasz 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to Interreg bureaucratic red tape, beneficiaries struggled with the stipulations of the project application itself (Shepherd and Ioanides 2020), the administration connected with the implementation (Cankar et al 2014), and different regulations (Menzel 2022). Filip et al (2020) found that 80% of experts found the administrative burden of project preparation and implementation as an obstacle that diminishes the interest in tourism cross-border cooperation projects. The EU survey on overcoming obstacles in border regions (EC 2016) also exposed the legal-administrative obstacles as the ones on the top of EU citizens' concerns when crossing EU borders.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors analyze some aspects of employment relations in the civil service in some European countries, the legal status of public authorities and employer, the activities of public institutions, the impact of public administration on sustainable development (Prusák, 1997;Cooper & Kaplan, 1999;Stillman, 2009;Peters & Pierre, 2014;Škultéty & Kaššák, 2014;Schwab, 2016;Shafritz et al, 2016;Urbancová & Hudáková, 2017;Peters & Pierre, 2017;Kabat, 2017;Pylypenko & Lytvynenko, 2017;Dalenogare et al, 2018, Ibarra et al, 2018Kuril, 2018;Filipová et al, 2019;Bai et al, 2020;Müller et al, 2021;Tugui et al, 2022;Pysmak et al, 2021;Sidak et al, 2021;Habib, 2022;Yermachenko et al, 2023;Ivanová & Žárská, 2023;Labunska et al, 2023;Crain et al, 2023;Timotius, 2023). This paper aims to conduct scientific research of terminus technicus "civil service", its most important institutes and competencies, as well as labour relations within the civil service, and based on the analysis of scientific knowledge about the current de lege lata legislation, to offer the authors' conclusions and prepare proposals de lege ferenda.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…For example, the US has a well-developed commercialization system through technology parks, incubators, and enabling legislation (such as the Bale-Dole Act) that allows universities to own and license intellectual property created with federal funding. The European Union focuses on improving the conditions for commercialization through various financial instruments and programs, such as Horizon Europe, which support innovative projects and cooperation between member countries (Filipová at al., 2019;Piccinetti et al, 2022). China considers the commercialization of research as part of its national development strategy and invests significant resources in supporting innovation and technology transfer.…”
Section: Source: Developed By the Authorsmentioning
confidence: 99%